2013
DOI: 10.1186/1475-2875-12-425
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of human Plasmodium knowlesi infections to anti-malarials

Abstract: BackgroundEvidence suggests that Plasmodium knowlesi malaria in Sarawak, Malaysian Borneo remains zoonotic, meaning anti-malarial drug resistance is unlikely to have developed in the absence of drug selection pressure. Therefore, adequate response to available anti-malarial treatments is assumed.MethodsHere the ex vivo sensitivity of human P. knowlesi isolates in Malaysian Borneo were studied, using a WHO schizont maturation assay modified to accommodate the quotidian life cycle of this parasite. The in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 33 publications
2
43
0
1
Order By: Relevance
“…Chloroquine and cycloguanil are fast-acting drugs which act in the first P. falciparum asexual intraerythrocytic developmental cycle (16,17), while clindamycin is a slow-acting drug with a "delayed-death" phenotype that is not observable until after two asexual intraerythrocytic developmental cycles (16). The activity of all three drugs was assessed against P. knowlesi A1H.1 using asynchronous parasites (0.25% parasitemia and 2% hematocrit) over 24 h, 48 h, or 72 h. Three independent assays (in triplicate wells) were carried out, and the resulting 50% inhibitory concentrations (IC 50 s) determined by log-linear interpolation (18) (20). While there were significant differences in the IC 50 s for cycloguanil at 24 h versus 48 h and 72 h (Table 1) (P Ͻ 0.05), there was no significant difference between the 48-h and 72-h IC 50 s (Table 1) (P ϭ 0.540).…”
mentioning
confidence: 99%
“…Chloroquine and cycloguanil are fast-acting drugs which act in the first P. falciparum asexual intraerythrocytic developmental cycle (16,17), while clindamycin is a slow-acting drug with a "delayed-death" phenotype that is not observable until after two asexual intraerythrocytic developmental cycles (16). The activity of all three drugs was assessed against P. knowlesi A1H.1 using asynchronous parasites (0.25% parasitemia and 2% hematocrit) over 24 h, 48 h, or 72 h. Three independent assays (in triplicate wells) were carried out, and the resulting 50% inhibitory concentrations (IC 50 s) determined by log-linear interpolation (18) (20). While there were significant differences in the IC 50 s for cycloguanil at 24 h versus 48 h and 72 h (Table 1) (P Ͻ 0.05), there was no significant difference between the 48-h and 72-h IC 50 s (Table 1) (P ϭ 0.540).…”
mentioning
confidence: 99%
“…Previous small studies have shown the efficacy of parenteral artesunate in treating severe knowlesi malaria, likely attributed to its fast parasite clearance properties 7. A study by Fatih et al 8 has shown that Plasmodium knowlesi is highly sensitive to artemisinins compared to chloroquine and mefloquine. An randomised controlled trial carried out by Dr Matthew J Grigg and his team, published in February 2016, has shown that artesunate-mefloquine was better compared to chloroquine monotherapy in uncomplicated Plasmodium knowlesi infection 9.…”
Section: Discussionmentioning
confidence: 99%
“…3,18 Consistently, in vitro drug susceptibility study has shown that P. knowlesi exhibited high sensitivity to artemisinins, whereas sensitivities to chloroquine and mefloquine were lower. 19 Therefore, parenteral artesunate has been recommended by the World Health Organization (WHO) as the treatment of choice for severe knowlesi malaria. 20 On the other hand, delay in diagnosis and treatment could lead to high parasite density that reportedly had a strong association with disease severity.…”
Section: Discussionmentioning
confidence: 99%